Environmental influence on the worldwide prevalence of a 776C→G variant in the transcobalamin gene (TCN2). Issue 6 (12th January 2007) - Guéant, Jean-Louis; Chabi, Nicodème W; Guéant-Rodriguez, Rosa-Maria; Mutchinick, Osvaldo M; Debard, Renée; Payet, Corinne; Lu, Xiaohong; Villaume, Christian; Bronowicki, Jean-Pierre; Quadros, Edward V; Sanni, Ambaliou; Amouzou, Emile; et al.
Abstract : Background: A 776C→G variant (dbSNP ID: rs1801198) in the transcobalamin gene ( TCN2 ; MIM# 275350) decreases the cellular and plasma concentration of transcobalamin and thereby influences the cellular availability of vitamin B12 . Objective: To evaluate the worldwide prevalence of this variant and its association with homocysteine plasma level. Methods: The study was performed in 1433 apparently healthy subjects, including Afro-Americans and Afro-Africans and in 251 Afro-Africans participants with severe malaria. Results: The frequencies of the 776G allele were the highest in China (0.607; 95% CI 0.554 to 0.659), low in West Africa (Bénin and Togo, 0.178; 0.154 to 0.206), and intermediate in France (0.445; 0.408 to 0.481), Italy (0.352; 0.299 to 0.409), Morocco (0.370; 0.300 to 0.447) and Mexico (0.374; 0.392 to 0.419). The 776G genotype was more frequent in Afro-Americans from New York (16.7; 8.4 to 30.7) and in Afro-African patients with severe malaria (6.0%; 95% CI 3.7 to 9.6) than in healthy Afro-African volunteers (p = 0.0004 and p = 0.033, respectively), while no difference was observed for MTHFR 677TT and 677T alleles. A disequilibrium of TCN2 genotype distribution was recorded in patients with severe malaria, with a twofold higher GG genotype than expected (p = 0.010). An association between the TCN2 polymorphism and homocysteine was observed only in Mexico and France, the two countries with the highest rate of low plasma concentration of vitamin B12 (<100 pmol/l). Conclusion: Given the dramatic heterogeneity of the 776G allele frequency worldwide, this polymorphism may be prone to a selective pressure or confers an evolutionary advantage in confronting environmental factors, one of which is malaria.